Antimicrobial resistance patterns and bacterial profiling among dental caries patients - Jaffar, Sumyya; Muhammad Kamran Taj; Muhammad Iqbal Khan; Masroora Ali Khan; Arsalan Ahmad Shah; Saima Azam (Journal of the Pakistan Medical Association, 2025)
Objective: To examine the prevalence of dental caries and their antibiotic resistance patterns. Method: The cohort study was conducted at the Centre for Advanced Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta, Pakistan, from November 2022 to April 2023, and comprised bacterial dental caries samples that were processed for different biochemical parameters and antibiotic susceptibility. Data was analysed using SPSS version 2022. Results: out of the 1,000 subjects from whom the samples were collected, 676(67.6%) were males and 324(32.4%) were females. Overall, 426(42.6%) subjects were aged 5-20 years. Of the total samples, 540(54%) were positive for pathogenic bacteria, with streptococcus mutans 256(25.6%) being the most common bacteria, followed by streptococcus mitis 194(19.4%), escherichia coli 69(6.9%) and pseudomonas aeruginosa 21(2.1%). Dental caries was more common among male patients 396 (73.3%), and the most affected age group was 5-20 years 261(48.3%). Illiterate patients 302 (56%) had more dental caries compared to the literate 238 (44.07%) patients. Antibiotic sensitivity tests revealed that most bacterial isolates were highly resistant to ampicillin, ciprofloxacin, and vancomycin. Conclusion: Dental caries mostly affected males and those aged 5-20 years. Most bacterial isolates were resistant to ampicilin, ciprofloxacin and vancomycin. Key Words: Anti-Bacterial, Vancomycin, Streptococcus mutans, Ciprofloxacin, Pseudomonas aeruginosa, Streptococcus mitis, Vaccinology, Dental Caries, Microbial, Ampicillin